Prevalence of vision impairment among patients with diabetes mellitus in sub-Saharan Africa: A systematic review and meta-analysis - Altaseb Beyene Kassaw; Addis Alem Hadigu; Melese Shenkut Abebe; Amare Abera Tareke; Wondwossen Debebe; Gosa Mankelkl; Natnael Kebede; Alemu Gedefie (PLoS ONE, 2025)
Background Diabetes mellitus is a growing global public health challenge, especially in low- and middle-income regions like sub-Saharan Africa, where healthcare resources are often limited. One of its most debilitating complications is vision impairment, which significantly impacts the quality of life, productivity, and independence of individuals. Although several studies have assessed the prevalence of vision impairment among individuals with diabetes in sub-Saharan Africa, their findings have been inconsistent and fragmented across different areas. A comprehensive synthesis of this evidence is crucial for informing healthcare planning, early screening, and management strategies. This study aimed to systematically review and synthesize the existing evidence on the prevalence of vision impairment among patients with diabetes mellitus in the region. Methods A literature exploration was done in an electronic database such as PubMed, Google Scholar, Web of Science, Hinary, and African Journals Online. We included all observational studies reporting the prevalence of vision loss among diabetes mellitus patients in Sub-Saharan Africa. A random-effect meta-analysis model was computed to estimate the pooled prevalence of vision impairment. I2 test and Cochrane Q test statistics were used to assess the heterogeneity of the studies. Subgroup analysis was done based on the countries where the research was conducted. STATA Version 16 statistical software was used for data analysis. Publication bias was examined by funnel plots and Egger’s tests. Results Only 26 studies with 12508 participants, contributing data from 14 countries within Sub-Saharan Africa, met the inclusion criteria for the final analysis. The overall pooled prevalence of visual impairment was found to be 29% (95% CI: 22%−35%). Heterogeneity was observed among included studies (p < 0.001 for high I2 values). Subgroup analysis revealed the source of heterogeneity in the studies carried out in Ethiopia (I2 = 99.2%, p = < 0.001), Nigeria (I2 = 94.59%, p = < 0.001), and Zambia (I2 = 77.34%, p = 0.036). Conclusion The findings of this study indicated that the pooled prevalence of vision impairment among diabetes mellitus patients is relatively higher. It can be concluded that diabetes mellitus patients should be managed properly to prevent visual impairment. Early detection of visual impairment through screening and regular follow-up is recommended to reduce as well as control the burden of visual impairment and its impact on the diabetic population.